Editorial: pattern formation in biology - Formosa Jordan, Pau (2023)
Over the past two decades, the study of pattern formation in biology has attracted the attention of many scientists from diverse fields, ranging from developmental biology, cell biology and synthetic biology, to physics, mathematics and computer science. Quantitative and interdisciplinary approaches have become essential for understanding these challenging phenomena. This Research Topic contains a collection of articles and reviews that use quantitative and interdisciplinary perspectives to understand the underlying mechanisms driving biological pattern formation. Modeling morphogenetic processes, gene regulatory network dynamics and morphogen gradients link the articles of this Research Topic, with a focus on three research areas: 1) underlying mechanisms of patterning processes; 2) cross-talk of morphogenetic and pattern formation processes, and 3) mathematical methods for modeling and quantifying biological patterning and morphogenesis. Below, each of the present Research Topic papers is briefly discussed.